2023
DOI: 10.1182/bloodadvances.2022007611
|View full text |Cite
|
Sign up to set email alerts
|

Chronic GvHD NIH Consensus Project Biology Task Force: evolving path to personalized treatment of chronic GvHD

Abstract: Chronic GvHD (cGvHD) remains a prominent barrier to allogeneic hematopoietic stem cell transplantion as the leading cause of non-relapse mortality and significant morbidity. Tremendous progress has been achieved in both understanding of pathophysiology and the development of new therapies for cGvHD. While our field has historically approached treatment from an empiric position, research performed at the bedside and bench has elucidated some of the complex pathophysiology of cGvHD. From the clinical perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 224 publications
0
2
0
Order By: Relevance
“…In particular, it was found that IL-1, IL-2, IL-6, IL-8, IL-10, IL-17, IP-10/CXCL-10, ICAM-1, TNF-a, EGF, lymphotoxina(LT-a), E-selectin (CD62E), B-cell activation factor (BAFF), and neuropilin-1 could be regarded as biomarkers of ocular GVHD for prediction, diagnosis, and prognosis (139,142,145,(150)(151)(152). In addition to their clinical utility, these biomarkers can identify potential therapeutic mechanisms and biological targets (153). For prediction, Cocho et al (143) generated predictive models based on the best panel of IL-8/CXCL8 and IP-10/CXCL10 tear levels along with age and sex, which showed good sensitivity (86.36%) and specificity (95.24%).…”
Section: Ocular Gvhd Biomarkersmentioning
confidence: 99%
“…In particular, it was found that IL-1, IL-2, IL-6, IL-8, IL-10, IL-17, IP-10/CXCL-10, ICAM-1, TNF-a, EGF, lymphotoxina(LT-a), E-selectin (CD62E), B-cell activation factor (BAFF), and neuropilin-1 could be regarded as biomarkers of ocular GVHD for prediction, diagnosis, and prognosis (139,142,145,(150)(151)(152). In addition to their clinical utility, these biomarkers can identify potential therapeutic mechanisms and biological targets (153). For prediction, Cocho et al (143) generated predictive models based on the best panel of IL-8/CXCL8 and IP-10/CXCL10 tear levels along with age and sex, which showed good sensitivity (86.36%) and specificity (95.24%).…”
Section: Ocular Gvhd Biomarkersmentioning
confidence: 99%
“…3,4 Despite significant progress in the classifications of cGvHD, there is a need for improved and practical prognostication systems to address interpatient variability and achieve the goal of personalized treatment. 5 In this study, we introduce red cell distribution width (RDW) as a new biomarker candidate that could enhance the development of personalized treatment strategies and risk stratifications for cGvHD. Red cell distribution width is a measure of the variation of the mean corpuscular volume of red blood cells (RBC) and is routinely reported in most standard complete blood count results.…”
mentioning
confidence: 99%